Adipose-Derived Mesenchymal Stem Cells Reprogram M1 Macrophage Metabolism via PHD2/HIF-1α Pathway in Colitis Mice - Yuan, Yin; Ni, Shuo; Zhuge, Aoxiang; Li, Lanjuan; Li, Bo (Frontiers in Immunology, 2022)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease worldwide. Infiltration of pro-inflammatory macrophages (M1 macrophages) contributes to the occurrence of bowel inflammation. Transplantation of mesenchymal stem cells (MSCs) is a promising therapeutic strategy for UC, but the exact mechanism remains unknow yet. Here, we treated DSS-induced colitis mice with adipose‐derived mesenchymal stem cells (ADMSCs) and revealed that ADMSCs alleviated colon inflammation by reducing the infiltration of M1 macrophages. Moreover, ADMSCs exerted this therapeutic effect by inhibiting succinate accumulation, increasing PHD2 to prevent M1 macrophages from overexpressing HIF-1α and thereby reprogramming the glycolytic pathway of M1 macrophages. Meanwhile, the succinate secreted by M1 macrophages triggered ADMSCs to secrete PGE2 in return, which could also shift macrophages from M1 phenotype to M2. Our work demonstrated an immunomodulatory effect of ADMSCs and provided a novel perspective on UC therapy.